Digital Literature Literacy (DLL) and Literature Digital Reading (LDR) in European Schools - Canals-Botines, Mireia; Raluy Alonso, Angel (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
DILECTINGS (Digital Literature Educational Competences for Teachers: Intercultural Inclusive Good Practices) is a European Key Action 2 Project that explores digital literature teaching. Digital literature—literature intended as authentic materials with cultural value—is an engaging and interactive narrative form delivered via digital media, that encompasses the language of books, films, web pages, radio, among others. This paper aims to present a preliminary questionnaire to explore the needs of primary and secondary teachers in terms of digital literature literacy and literature digital reading. This article will show the questionnaire design process to carry out a proper needs analysis.